Assistance in Revitalizing the Field in Ngepungsari Village, Jatipuro District, Karanganyar Regency - Handoyo, Suryo; Susila, Herman; Mulyandari, Erni (Devotion : Journal of Community Service, 2022)
Assistance for the Revitalization of the Ngepungsari Village Field is carried out to assist the community in the Ngepungsari Village, Jatipuro District, Karanganyar Regency in terms of increasing economic income and tourism development by revitalizing the field into a tourist market. This development is done independently. The difficulty faced by the community in planning this field revitalization is how to make a good market design plan according to the needs and potential of the Ngepungsari community as well as a tourist destination in the village. With this market, it is hoped that the villagers' produce can be sold through the tourism market and at the same time it can attract both domestic and international tourists to Ngepungsari Village so as to increase the economic income of Ngepungsari villagers.